MEMBANGUN KESETARAAN GENDER DALAM PEMBELAJARAN SAINS: STUDI IDENTITAS SAINS SISWA DI SEKOLAH MENENGAH SWASTA DI TANGERANG SELATAN - Toni Hidayat (Haga : Jurnal Pengabdian Kepada Masyarakat, 2023)
Science education plays a crucial role in preparing young generations to face global challenges; however, the gender gap in this field remains a significant issue. This study aims to explore the science identity of students in private secondary schools in South Tangerang and identify the factors influencing gender equality in science education. The activities involved 150 students, including 75 male and 75 female students, as well as teachers and parents in a series of workshops, outreach sessions, and mentoring programs. The results show that female students experienced increased motivation and confidence in science after participating in the program, while teachers and parents became more aware of the importance of equitable support for all students. These findings highlight the need for an inclusive learning approach and recommendations for developing a fairer curriculum. Through this initiative, it is hoped that better gender equality in science education can be achieved, allowing all students to reach their potential.